The microbiota in feces of domestic pigeons in Seoul, Korea. Issue 4 (April 2023) - Oh, Singeun; Park, Shin Hye; Choi, Jun Ho; Kim, Soo Lim; Kim, Myungjun; Lee, Seogwon; Yi, Myung-hee; Lee, In-Yong; Yong, Tai-Soon; Kim, Ju Yeong
Abstract: In Korea, feral pigeons pose significant public health risks because they carry various zoonotic pathogens. Human population density is a significant factor in zoonotic disease events. Seoul is one of the largest cities by population density among developed countries and where most of the homeless population in Korea exists. We designed this study to compare the microbiota of pigeon feces by regional characteristics and the presence of homeless individuals. Therefore, this study used 16S rRNA amplicon sequencing to detect possible pathogenic microbes and assess the current risk of zoonosis in Seoul, South Korea. Pigeon fecal samples (n = 144) obtained from 19 public sites (86 and 58 fecal samples from regions in and outside Seoul, respectively) were examined. Potentially pathogenic bacteria were also detected in the fecal samples; Campylobacter spp. was found in 19 samples from 13 regions, Listeriaceae was found in seven samples, and Chlamydia spp. was found in three samples from two regions. Principal coordinates analysis and permutational multivariate analysis of variance revealed a significant difference in bacterial composition between the regions in Seoul (n = 86) and outside Seoul (n = 58) and between the regions with (n = 81) and without (n = 63) homeless individuals. Overall, this study identified various potentially pathogenic microorganisms in pigeon feces at public sites in South Korea. Moreover, this study demonstrates that the microbial composition was influenced by regional characteristics and homelessness. Taken together, this study provides important information for public health strategic planning and disease control. Highlights: Potential pathogenic microbes were identified in pigeon feces in Seoul, South Korea. Microbial compositions of fecal samples differed with location. Lactobacillus and Escherichia-Shigella were the two most abundant microbes. Campylobacter spp., Listeriaceae, Chlamydia spp. (potentially pathogenic) were found. Microbiota varied between locations with and without homeless people.